The effect of radiological distribution on the COVID-19 disease - Kuluozturk, Mutlu; In, Erdal; Turgut, Teyfik; Aydin, Aye Murat; Toraman, Zulal Asci; Deveci, Figen (Turkish Assoc Tuberculosis & Thorax, 2021)
Introduction: The aim of the study was to investigate the effects of radiological distribution on COVID-19 clinic and prognosis and to determine the relationship between laboratory parameters and thorax CT findings. Materials and Methods: Patients with COVID-19 were evaluated retrospectively. laboratory parameters were obtained from medical records. Ground-glass opacities (GGO) and consolidation were evaluated on thorax CT. The presence of a single lobe lesion was considered as limited while multiple lobe lesions were considered as diffuse involvement for both GGO and consolidation. Results: A total 200 patients with COVID-19 were evaluated. 178 of them (89%) were discharged, 17 patients (8.5%) were transferred to the ICU and five patients died (2.5%). The ratios of mortality and transfer to the ICU in patients with diffused GGO were significantly higher compared to patients with limited GGOs. It was observed that troponin >= 0.06 mu g/L, platelet <140 and fibrinogen >= 350 mg/dl were independent predictors of the presences of diffused GGOs in thorax CT. Conclusion: Diffused GGOs on thorax CT are correlated with the rate of mortality and transfer to the ICU in patients with COVID-19. Also, troponin, fibrinogen, and platelet levels can be used while predicting extensive parenchymal disease on thorax CT.
Radyolojik dağılımın COVID-19 hastalığına etkisi
Keywords: COVID-19; thorax CT; troponin; fibrinogen; platelet levels